Data Acquisition System Based On FPGA - Mahrus, Nuril Syahira (Universiti Sains Malaysia, 2005)
For undergraduate project, a data acquisition system based on FPGA has been developed. An analog data, which comes from power supply (in voltage signals) is gathered and then be converted to digital signals. This is done by ADC0809. This system is fully controlled by FPGA using the Xilinx Foundation Series 2.1, by Project Manager. The device used is XC4010 PC84 and the language used to develop the coding is VHDL code. Data from the ADC0809 (which is in digital form) will be processing to make sure that it can appear on LCD. To do this, the data first must be converted from the Hex code to the ASCII code. After the data has been converted to ASCII code, then it will be displayed on the LCD. At the same time, the data will be compared to a fix variable, which is 3F in Hex and equal to 1.24V. If the data is beyond the variable then LED will turning ON, and if the data is less than that (the variable), then the LCD will not turning ON. It is designed to show the monitoring system.